DETERMINASI INTEGRITAS LAPORAN KEUANGAN DI INDONESIA - Intan Nurul Oktaviani (2020)
This study was conducted to determine the effect of independent commissioners, institutional ownership, managerial ownership, audit quality, auditor industry specialization, and company size on the integrity of financial statements. The population in this study are non-financial public listed companies listed on the Indonesia Stock Exchange in the period 2016 - 2018 as many as 591 companies. Sampling was done through a purposive sampling method and collected 400 research data samples. Hypothesis testing in this test uses Multiple Linear Regression Analysis with SPSS version 25 and a significance level of 5% (0.05). R square adjusted value of 36.9%, meaning that the integrity of the financial statements is influenced by the variables in this study. The results of the test show that: 1) independent commissioners and auditor industry specialization have a significant negative effect on the integrity of financial statements; 2) institutional ownership, audit quality and company size have a significant positive effect on the integrity of financial statements; 3) managerial ownership does not affect the integrity of financial statements.